The Problems of The Illegitimate Child (Walad al-zina) Foundling (Laqit) int The Sunni Schools of Law - Mohamad Sujimon (IIUM Press, 2010)
This Book Addresses the views of the sunni scholars regarding the importance of genealogical relationship (nasab) in Islamic family law and examines the role of legatimicy on the basis of the legal maxim "al-walad li al-firash"